2008
DOI: 10.1177/1367006908098564
|View full text |Cite
|
Sign up to set email alerts
|

Phonological acquisition in Malta: A bilingual language learning context

Abstract: A total of 241 Maltese children aged 2;0-6;0 years, drawn randomly from the public registry of births, were assessed on a picture naming task to evaluate phone articulation, phonology and consistency of word production. Children were allowed to use the language they chose (either Maltese or English). Ninetythree children (38.6%) were reported by parents to speak both Maltese and English at home, 137 (56.9%) were reported to speak Maltese and 11 (4.7%) only English at home. The data gained were analyzed for per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 28 publications
7
59
0
Order By: Relevance
“…The results obtained here then appear to be in line with a growing number of studies that have indicated accelerated rates of phonological acquisition in bilinguals compared with age-matched monolinguals (Goldstein & Bunta, 2012;Grech & Dodd, 2008;Kehoe et al, 2001;Lleó et al, 2003;Tamburelli et al, 2012). In view of other studies reporting delayed acquisition by bilinguals (Dodd et al, 1996;Fabiano-Smith & Goldstein 2010;GildersleeveNeumann et al, 2008;Goldstein & Washington, 2001), what then can account for the WelshEnglish bilingual children's apparent enhanced performance on English word-final clusters?…”
Section: Rate Of Acquisitionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results obtained here then appear to be in line with a growing number of studies that have indicated accelerated rates of phonological acquisition in bilinguals compared with age-matched monolinguals (Goldstein & Bunta, 2012;Grech & Dodd, 2008;Kehoe et al, 2001;Lleó et al, 2003;Tamburelli et al, 2012). In view of other studies reporting delayed acquisition by bilinguals (Dodd et al, 1996;Fabiano-Smith & Goldstein 2010;GildersleeveNeumann et al, 2008;Goldstein & Washington, 2001), what then can account for the WelshEnglish bilingual children's apparent enhanced performance on English word-final clusters?…”
Section: Rate Of Acquisitionsupporting
confidence: 88%
“…Some studies on bilinguals include information on clusters alongside other areas of phonological development (Grech & Dodd, 2008;. For example, Holm and Dodd (1999) report that the Cantonese-English bilingual children in their study reduced Cantonese /kw-/ to [t], but English /kw-/ to [w], exhibiting language-specific differences in error patterns.…”
Section: Consonant Cluster Acquisitionmentioning
confidence: 99%
“…, , , Munro et al . ), and 93 bilingual children in Malta (Grech and Dodd ). Other characteristics of speech production that have been investigated are voice onset time (VOT), voice pitch, rhythm, prosody and fluency (Deutchar and Clark , Fokes et al .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we need to adapt to this diversity. For example, the current data on bilingual speech and language acquisition is indicating that bilingual children have different patterns and rate of acquisition of such skills (e.g., Grech & Dodd, 2008;Stow & Pert;So & Leung, 2006;Salameh, Nettlebladt, & Norlin, 2003). SLPs need to adapt and adopt tools to assess and manage the culturally and linguistic diverse populations to whom they are increasingly being referred.…”
Section: Training Health Care Professionals To Address Needs Of the Cdpmentioning
confidence: 99%